Hubungan Antara Kepercayaan Diri Dengan Kecemasan Menghadapi Pertandiangan pada Atlet Bulu Tangkis PB Indocafe di Medan - Ririn Sitinjak; Azhar Azis; Faridah Hanum; Babby Hasmayni (Universitas Medan Area, 2023)
This study aims to determine the relationship between self-confidence and anxiety in facing a match. The scale used in this study is the self-confidence scale and the anxiety scale where the subjects in this study are PB Indocafe badminton athletes in Medan, totaling 30 athletes. The data analysis method used in this study is a purposive sampling technique, so the following results can be obtained: the hypothesis proposed in this study reads